(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
INTRODUCTION: Thyroid hormones are important metabolic regulators having direct and indirect action on lipid production, disposal and efflux. It may be associated with dyslipidaemia, leading to the associated risks of coronary artery diseases and atherosclerosis. To date this has not been clearly elucidated in Indian populations which are considered to be a high risk group when it comes to Coronary Artery Disease. We in our study have tried to elaborate and find a relationship between Subclinical Hypothyroidism and Dyslipidaemia. OBJECTIVE: To study the association of subclinical hypothyroidism with dyslipidaemia using a normothyroid group as control population. METHOD: Ours is a cross sectional observational study undertaken after approval of the Institutional Review Board. After due consent and verification of the inclusion and exclusion criteria, 100 normothyroid and 100 naïve subclinical hypothyroid patients were considered for the study and their fasting lipid profile checked. The data was compiled and after appropriate statistical analysis inferences were drawn. RESULTS: Our study demonstrated a statistically significant difference in the lipid profile and composition of the two groups with the Subclinical hypothyroid having a higher prevalence of dyslipidaemia. CONCLUSIONS: We were able to demonstrate significantly higher levels of prevalence of dyslipidaemia in the subclinical hypothyroid group as compared to the general population. This is of interest as this group of patients are not targeted for therapy. Further research using larger data pools is required to formulate treatment goals and to evaluate the need for screening SCH patients for dyslipidaemia which may help in preventing and reducing the CAD burden.